Program Pendampingan Kegiatan Ramadhan sebagai Madrasah Spiritual dalam Membentuk Karakter Islam Siswa di Madrasah Ibtidaiyah Nurul Ikhlas Tambak Sawah Waru Sidoarjo - Anggraini Novita Sari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The article aims to analyze the implementation of the Ramadan activity mentoring program as a spiritual madrasa in shaping the Islamic character of students at Madrasah Ibtidaiyah Nurul Ikhlas Tambak Sawah Waru Sidoarjo. This study uses a descriptive approach with the Asset-Based Community Development (ABCD) method through the stages of discovery, dream, design, define, and do. Data collection techniques were carried out through observation. The results of the activities show that structured Ramadan activities have a positive impact on students, as seen from high attendance as well as improvements in discipline and responsibility, particularly in performing religious activities such as tadarus, congregational prayers, and memorization. This activity is also able to increase religious awareness as well as foster a sense of togetherness and social care within the madrasah environment. However, this study has limitations due to the very small number of subjects, so the results cannot yet be generalized widely, as well as the implementation time that only took place during the month of Ramadan, which has not been able to depict long-term changes in student behavior. Therefore, it is recommended that future activities involve a larger number of respondents and a longer observation period so that the results obtained are more comprehensive